(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Currently, acute respiratory infections (ARI) are a significant pathology of childhood (they account for up to 90% of all cases of acute respiratory tract infections). The effectiveness of probiotics in various diseases has been proven, however, the possibilities of using probiotics as a preventive agent and a method of increasing the body’s anti-infectious resistance in acute respiratory infections are becoming increasingly important. In numerous clinical studies involving children, it was found that probiotics contributed to a reduction in the number of cases of acute respiratory infections, a decrease in the average duration of an episode of acute respiratory infections and the frequency of antibiotic use, as well as a decrease in the number of missed classes in preschool/school related to colds. Careful selection of probiotic strains, taking into account their safety for the human body and good tolerability, the multidirectional and physiological action of probiotics contributed to the appearance on the market of a number of probiotics with proven clinical efficacy. This article presents the basic information confirming the effectiveness of the use of Lactobacillus plantarum No. 7315/7316 in clinical practice.